FINANCIAL RESOURCES FOR REGIONAL ECONOMY - S. L. Orlov (Russian Journal of Economics and Law)
On the basis of factual material and theoretical investigations the article views the most important elements of forming of a competitive financial service system in Tatarstan Republic as an inseparable part of the Russian financial market.